PEMBIASAAN TILAWAH AL-QUR’AN SEBAGAI DETERMINAN KONSENTRASI BELAJAR SISWA MADRASAH IBTIDAIYAH - Mokhamad Choirul Hudha (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Learning concentration is a crucial prerequisite for students' academic success, yet attention degradation has become a serious challenge in the digital era. This study aims to analyze the influence of Quranic recitation habituation on the learning concentration of students in Madrasah Ibtidaiyah. Using a causal-associative quantitative approach, this research involved upper-grade students as samples selected through purposive sampling techniques. Data were collected through recitation habituation questionnaires, structured observations, and the Grid Concentration Test. Data analysis was performed using simple linear regression and the coefficient of determination. The results indicated that the habituation of Quranic recitation significantly acts as a positive determinant of learning concentration. Neuro-pedagogically, consistent morning recitation is able to condition alpha brainwaves that support cognitive readiness. Furthermore, precision in Tajwid was found to correlate with students' attentional sharpness in understanding lesson instructions. This study recommends the implementation of routine recitation as an attention management strategy within the madrasah environment.